2017
DOI: 10.1016/j.jns.2017.02.046
|View full text |Cite
|
Sign up to set email alerts
|

Multimodal and simultaneous assessments of brain and spinal fluid abnormalities in chronic fatigue syndrome and the effects of psychiatric comorbidity

Abstract: The purpose of this study was to investigate whether CFS patients without comorbid psychiatric diagnoses differ from CFS patients with comorbid psychiatric diagnoses and healthy control subjects in neuropsychological performance, the proportion with elevated spinal fluid protein or white cell counts, cerebral blood flow (CBF), brain ventricular lactate and cortical glutathione (GSH). The results of the study did not show any differences in any of the outcome measures between CFS patients with and without psych… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 20 publications
0
10
0
Order By: Relevance
“…Using MR spectroscopy, lower N-acetylaspartate concentration in the hippocampus [ 50 ], lower cortical glutathione levels [ 51 , 52 ], higher choline concentration in the basal ganglia [ 53 ], higher lactate concentrations in the lateral ventricles (from a same group) [ 51 , 52 , 54 56 ], higher choline to creatine ratio in the occipital cortex [ 57 ] have been reported in ME/CFS. No differences in -aminobutyric acid nor glutamate + glutamine either in the occipital cortex or anterior cingulate cortex [ 55 ] or N-acetylaspartate to creatine ratio in the frontal and occipital cortex [ 57 ] have been reported.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Using MR spectroscopy, lower N-acetylaspartate concentration in the hippocampus [ 50 ], lower cortical glutathione levels [ 51 , 52 ], higher choline concentration in the basal ganglia [ 53 ], higher lactate concentrations in the lateral ventricles (from a same group) [ 51 , 52 , 54 56 ], higher choline to creatine ratio in the occipital cortex [ 57 ] have been reported in ME/CFS. No differences in -aminobutyric acid nor glutamate + glutamine either in the occipital cortex or anterior cingulate cortex [ 55 ] or N-acetylaspartate to creatine ratio in the frontal and occipital cortex [ 57 ] have been reported.…”
Section: Resultsmentioning
confidence: 99%
“…Eight studies observed decreased global or regional CBF in ME/CFS [ 17 , 18 , 51 , 52 , 66 69 ]. Peterson et al observed reduced cerebral perfusion in 3 of 10 at rest and 6 of 10 patients with ME/CFS after an exercise of walking 1.61 km/hour for 30 min while only in 2 of 10 HCs at rest and post-exercise [ 70 ].…”
Section: Resultsmentioning
confidence: 99%
“…• Increased nitrosative stress: increased levels of inducible nitric oxide synthase (iNOS), possibly secondary to increased production of NFκB [108]; increased nitric oxide (NO), peroxynitrite, and nitrate, particularly following exercise [109]. • Brain magnetic resonance imaging (MRI) has shown elevated levels of ventricular lactic acid consistent with oxidative stress [110,111].…”
Section: Metabolomic Abnormalities In Me/cfsmentioning
confidence: 99%
“…ME/CFS patients have a number of pathophysiological traits that point to abnormalities in the ANS, including impaired blood pressure variability, orthostatic intolerance, high prevalence and severity of posturalorthostatic tachycardia syndrome (POTS), delayed gastric emptying, impaired thermoregulation in adolescent patients, loss of capacity to recover from acidosis on repeat exercise, abnormal cardiac output and altered brain characteristics in a wide variety of brain regions including the limbic system structures that govern the ANS (1,(78)(79)(80)(81). These altered brain characteristics include reduced cerebral, brainstem, and cerebral cortex blood flow; impaired reciprocal connectivity between the vasomotor center, midbrain, and hypothalamus regions; increased neuroinflammation across widely distributed brain areas including but not limited to the hippocampus, thalamus, midbrain and pons; reduced cerebral glucose metabolism, and lower brain glutathione (1,(82)(83)(84)(85)(86). Many of the altered brain characteristics seen in ME/CFS patients are similarly reported in clinical cases associated with neurotropic enteroviruses.…”
Section: Enterovirus Cell and Tissue Tropismmentioning
confidence: 99%